Oral fluoroquinolones and the incidence of rhegmatogenous retinal detachment and symptomatic retinal breaks: a population-based study - Kapoor, Kapil G. (Ophthalmology, 2014)
OBJECTIVE: To examine whether oral fluoroquinolone antibiotics are associated with an increase in subsequent rhegmatogenous retinal detachment and symptomatic retinal breaks in a large, population-based cohort. DESIGN: Population-based cohort study PARTICIPANTS AND CONTROLS: Adult residents of Olmsted County, Minnesota who were prescribed oral fluoroquinolone medications from 1/01/03 – 6/30/11. Comparison cohorts consisted of patients prescribed oral macrolide and β-lactam antibiotics during the study period. METHODS: Procedure codes were used to identify retinal detachment repair and prophylaxis procedures occurring within 1 year of prescription dates. Travel clinic, pro re nata, and self-treatment prescriptions were excluded. Patients with tractional retinal detachment, previous retinal detachment repair, endophthalmitis, and necrotizing retinitis were excluded, as were those with intraocular surgery or severe head/eye trauma ≤ 90 days prior to the procedure. MAIN OUTCOME MEASURES: Rates of retinal detachment repair and prophylaxis procedures within 7, 30, 90, and 365 days of the first prescription were calculated and compared between antibiotic prescription cohorts using Chi-square tests. Retinal detachment repair rates were also compared to the expected Olmsted County, Minnesota rates using the one-sample log rank test. RESULTS: Oral fluoroquinolones were prescribed for 38,046 patients (macrolide n=48,074, β-lactam n=69,079) during the study period. Retinal detachment repair procedures were performed within 365 days of the first prescription in 0.03% (95% confidence interval [CI] 0.01–0.06%) of the fluoroquinolone, 0.02% (95% CI 0.01–0.03%) of the macrolide, and 0.03% (95% CI 0.02–0.05%) of the β-lactam cohorts (p>0.05). Retinal detachment prophylaxis procedures for symptomatic retinal breaks were performed within 365 days of the first prescription in 0.01% (95% CI 0.00–0.03%) of the fluoroquinolone, 0.02% (95% CI 0.01–0.04%) of the macrolide, and 0.02% (95% CI 0.01–0.04%) of the β-lactam cohorts (p>0.05). Similar comparisons of treatment rates within 7, 30, and 90 days of the first prescription were all non-significant between cohorts. Post-fluoroquinolone retinal detachment repair rates were similar to expected rates (36.8 per 100,000/year vs 28.8 per 100,000/year for age- and sex-matched historical rates, p = 0.35). CONCLUSIONS: Oral fluoroquinolone use was not associated with an increased risk of rhegmatogenous retinal detachment or symptomatic retinal breaks in this population-based study.